Urban Development Plan in the Greater Metropolitan Area - Rodríguez, Francisco (2007)
It is described how has been the urbanization development in Costa Rica in the last years and which has been the few planned actions towards that. It is analyzed some concepts referred to the “desirable city” that modern urbanistic paradigms offer, and how to reach it. It is described some politics impulsed in last twenty years in the Great Metropolitan Area (GAM), beginning with Gam Plan, from 1982, and some concepts that are replaced from this, taken from phases I and II of the –in progress- Plan Nacional de Desarrollo Urbano (National Plan of Urban Development). It is exposed the proposal in gestation of the Regional Urban Project of the GAM. Finally, recommendations are presented along the lines of a accomplishment of more human cities, more competitive and with a higher life quality.